2016
DOI: 10.1177/0309364614556836
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of questionnaires to assess patient satisfaction with limb orthoses

Abstract: Given the importance of analysing patient satisfaction with orthosis (PSwO), appropriate instruments to assess outcome are needed. This article reviews the currently available instruments and reflects on how future studies could be focused on the development, refinement and validation of outcome measures in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 116 publications
(346 reference statements)
1
42
0
3
Order By: Relevance
“… 32–34 Also a systematic review of questionnaires used to assess patient satisfaction with orthoses for any limb found that 63% of the 106 included papers used questionnaires developed for the specific study rather than validated measures, supporting our findings on this aspect of the evidence. 35 …”
Section: Discussionmentioning
confidence: 99%
“… 32–34 Also a systematic review of questionnaires used to assess patient satisfaction with orthoses for any limb found that 63% of the 106 included papers used questionnaires developed for the specific study rather than validated measures, supporting our findings on this aspect of the evidence. 35 …”
Section: Discussionmentioning
confidence: 99%
“…4,17,21 A systematic review of questionnaires that was used to assess patient satisfaction with any limb orthoses found that 63% of the 106 included papers used questionnaires that had been developed for the specific study rather than validated measures, indicating that our findings related to orthoses for knee instability is a broader issue in the field. 79 …”
Section: Findings In the Context Of Other Studiesmentioning
confidence: 99%
“…Walking distance 1 (improved) Walking speed 0 (no difference) Sensation of recurvatum 2 (much improved) Self-confidence when walking 1 (improved) Safety when walking 2 (much improved) *Subjective gait parameters were rated without and with the KAFO as: "much improved" (+2), "improved" (+1), "no difference" (0), "worse" (-1), "much worse" (-2) (15,19), and only scored by patients.…”
Section: Resultsmentioning
confidence: 99%
“…The Quebec User Evaluation of Satisfaction with assistive Technology (QUEST) was used to measure patient satisfaction with the orthosis. This questionnaire comprises 12 satisfaction items (8 questions about the orthotic device, its dimensions, its weight, whether it was easy to adjust, its safety and security, its durability, whether it was easy to use, comfort, and effective ness, and 4 questions about the services involved: its delivery, repairs and maintenance, and the professional services and fol low up services), where all the responses to these items give a quantitative score (19,34), as follows: 1: "not satisfied at all"; 2: "not very satisfied"; 3: "more or less satisfied"; 4: "quite satisfied"; and 5: "very satisfied".…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation